Technological innovation as a source of Chinese multinationals' firm-specific advantages and internationalization. Issue 1 (24th January 2019) - He, Shaowei; Khan, Zaheer; Lew, Yong Kyu; Fallon, Grahame
Abstract : Purpose: The purpose of this paper is to examine how innovation-related firm-specific ownership advantage (FSA) plays a role in developing the competitive advantage of Chinese multinationals when they internationalize. Design/methodology/approach: Based on a review of the existing literature concerning foreign direct investment by emerging economy multinational enterprises (EMNEs), the authors identify that numerous studies explain this phenomenon on the basis of their location-bound country-specific advantages. However, such views do not fully explain the key underlying factors behind the rapid rise and success of many EMNEs as these firms rapidly internationalize and develop global competitiveness in developed markets. The current research explores three leading innovative Chinese EMNEs from the engineering sector: BYD, Sany Heavy Industry and CSR China. Findings: The authors find that EMNEs' knowledge, and particularly their innovation-creating technological knowledge, has contributed greatly to their successful internationalization. The illustrative cases show that the three firms have now moved beyond the infant to the mature stage of EMNE development through developing their technological knowledge in order to realize FSA through internationalization. This study helps in contributing fresh reflections to the continuing debate concerning the causes of internationalization and global competitive development by EMNEs and the role of their FSAs in these processes. Originality/value: This is one of the few studies which have demonstrated that some of the EMNEs do possess firms' specific advantage which helps explain their innovative capabilities, competitive advantages and subsequent internationalization patterns.